Sappho's missed communications - Brian Bebbington (Peoples' Friendship University of Russia (RUDN University), 2017)
The premise of the study is that poets strive in their communications to convey meanings that are intensely personal to themselves, in language which is communal. The concept of love was chosen as exemplar as this is perhaps the most human of emotions, universal in experience and traditionally supposed therefore to be so in language. The study indicates the discontinuities that exist within cognition of the concept, however, synchronically and diachronically as demonstrated by the poetry of Sappho. Although theoretically a poet's communication is accessible to readers through a shared language, authors' and readers' experiences of that language are embedded in phenomena which, at their most intensely personal level, are mutually irreconcilable.